Study of Purse Seine Fishing Ship Trimaran Seakeeping with Axe-Bow and Without Axe-Bow Model Using Computational Fluids Dynamics - Richard Benny Luhulima; Fella Gaspersz; Agustinus Tupamahu; Simon Tubalawony (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Maluku waters are dominated by extreme weather conditions with wave heights of 1-5 meters. Purse seine fishingvessel is one type of fishing vessel that has very poor transverse stability. One way to improve the stability of theship is to change the shape of the monohull ship to a ship with a trimaran hull type. This research was focused onexamining the movement characteristics of purse seine fishing vessels with trimaran hull type with Axe-Bowmodification on the bow and without Axe-bow, through computational fluid dynamics. The use of Axe-bow ontrimaran is able to significantly reduce RMS Pitch, which is an average of 13.35% smaller when compared to Trimaranwithout Axe-bow. On the RMS Heave Trimaran Axe-bow can reduce an average of 5.27% if the Trimaran is withoutAxe-bow. Furthermore, the Trimaran Axe-bow is also able to reduce the RMS Roll by an average of 3.98% comparedto the Trimaran without Axe-bow. The results of this study can provide an initial description of the advantages ofusing the Axe-Bow on the Purse seine fishing trimaran ship.